2022
DOI: 10.3390/membranes12020122
|View full text |Cite
|
Sign up to set email alerts
|

Desalination Characteristics of Cellulose Acetate FO Membrane Incorporated with ZIF-8 Nanoparticles

Abstract: Forward osmosis membranes have a wide range of applications in the field of water treatment. However, the application of seawater desalination is restricted, so the research of forward osmosis membranes for seawater desalination poses new challenges. In this study, zeolitic imidazolate framework-8 (ZIF-8) was synthesized by a mechanical stirring method, and its crystal structure, surface morphology, functional group characteristics, thermochemical stability, pore size distribution and specific surface area wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 65 publications
(72 reference statements)
4
11
0
Order By: Relevance
“…However, upon the incorporation of ZnO-NPs into the CA-based film, its surface character changed from hydrophilic to hydrophobic, since the WCA increased to 92.1, indicating the hydrophobicity of ZnO-NPs. Similar results have been reported regarding the contribution of nanoparticles that lead to the enhancement of the hydrophobicity or impairment of the hydrophilicity of the membrane surfaces with increasing WCA values [ 73 ], such as the incorporation of silica nanoparticles (Si-NPs) into CA/CH-based films (CA/CH-Si) [ 79 ], and Cu-NPs into CA-based films [ 80 ]. On the other hand, the CH-based neat film seemed to be more hydrophilic, with the WCA ≈ 74.2°.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…However, upon the incorporation of ZnO-NPs into the CA-based film, its surface character changed from hydrophilic to hydrophobic, since the WCA increased to 92.1, indicating the hydrophobicity of ZnO-NPs. Similar results have been reported regarding the contribution of nanoparticles that lead to the enhancement of the hydrophobicity or impairment of the hydrophilicity of the membrane surfaces with increasing WCA values [ 73 ], such as the incorporation of silica nanoparticles (Si-NPs) into CA/CH-based films (CA/CH-Si) [ 79 ], and Cu-NPs into CA-based films [ 80 ]. On the other hand, the CH-based neat film seemed to be more hydrophilic, with the WCA ≈ 74.2°.…”
Section: Resultssupporting
confidence: 75%
“…The WCA of the food packaging films is used to determine the wettability of the film surface and evaluate its hydrophobic/hydrophilic character [ 65 ]. A hydrophilic surface is characterized by a smaller drop contact angle (an acute angle inside the drop or <90°), whereas a hydrophobic surface is characterized by a greater drop contact angle (obtuse angles or >90°) [ 65 , 73 ]. Figure 4 displays the WCAs of neat and composite films with ZnO-NPs, while Table 1 presents their respective mean values.…”
Section: Resultsmentioning
confidence: 99%
“…In the design of food packaging films, the WCA plays an important role, indicating the hydrophilic/hydrophobic character or the surface’s wettability [ 51 ]. Hydrophilicity and hydrophobicity are related to WCA values, thus the smaller the angle (acute angle inside the drop), the greater the hydrophilicity, whereas the greater the angle (obtuse angles or over 90 °), the greater the hydrophobicity [ 51 , 66 ]. The water contact angles of neat films and composite films are illustrated in Figure 3 , and their corresponding values are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…This value is significantly higher than that of commercial material. It has been reported that hydrophobic nanoparticles increase water contact angles when exposed to membrane surfaces [ 66 ]. Similar findings were reported for the incorporation of Cu-NPs into cellulose acetate films [ 72 ] and silica particles into cellulose acetate/chitosan films (CA/CS-Si) [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…55 According to WCA values, hydrophilicity, and hydrophobicity are determined by the angle inside a drop in contact with a film surface (hydrophilic surface < 90 < hydrophobic surface), and the increase in this angle indicates a higher degree of hydrophobicity. 55,60 Figure 1 shows the WCA values of neat PCL and composite membranes (PCL/GMIONPs and PCL/CMIONPs, respectively), and Table 1 provides the mean WCA values of each system. The measured WCA value for the neat PCL (118.9 ± 0.8 ) was consistent with its hydrophobic properties.…”
Section: Water Contact Anglementioning
confidence: 99%